POSTPARTUM ENDOMETRITIS IN COWS THEIR ECONOMIC EFFECTIVENESS IN TREATMENT WITH DIFFERENT METHODS - Niyazov H.B.; S. B. Abdiev (Galaxy International Interdisciplinary Research Journal, 2023)
In the first group of animals with catarrhal endometritis, the treatment lasted an average of 8 days, in the second group, 10 days, and in the third group, 13 days, and in the first group of animals with purulent-catarrhal endometritis, the treatment lasted 9 days, in the second group, 11 days, and in the third group, 14 days. In animals with purulent-catarrhal endometritis of fungal etiology, using the improved method of treatment of endometritis in cows for 11, 13 and 15 days will prevent economic damage from 823,845 soums per head of milk cow, as well as an average of one per head of milk cow. allows to get economic benefit from 1617890 soums per year, and in this case the cost coverage is 3.9 soums.